2016
DOI: 10.1111/jnc.13736
|View full text |Cite
|
Sign up to set email alerts
|

Novel incretin analogues improve autophagy and protect from mitochondrial stress induced by rotenone inSHSY5Y cells

Abstract: Currently, there is no viable treatment available for Parkinson's disease (PD) that stops or reverses disease progression. Interestingly, studies testing the glucagon-like-peptide-1 (GLP-1) mimetic Exendin-4 have shown neuroprotective/neurorestorative properties in pre-clinical tests and in a pilot clinical study of PD. Incretin analogues were originally developed to treat type 2 diabetes and several are currently on the market. In this study, we tested novel incretin analogues on the dopaminergic SH-SY5Y neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 68 publications
2
49
0
Order By: Relevance
“…Furthermore, CREB can be activated and sustained by the CaMKII cascade (Ao, Ko, & Zhuo, ) and the activation of CREB by phosphorylation at Ser133 ( S133 p‐CREB) is critical for memory formation and LTP maintenance, because the downstream genes are involved in synaptic formation, neuronal plasticity and neurogenesis (Deisseroth et al, ). This study supports the conclusion above and provides a proof that the transcription factor CREB, part of this signaling pathway (Jalewa, Sharma, & Hölscher, ), was also re‐activated by the novel triagonist in the APP/PS1 AD mice. GSK‐3, a multifunctional kinase, phosphorylates the tau protein which aggregates to tangles in the AD brain (Perez‐Costas, Gandy, Melendez‐Ferro, Roberts, & Bijur, ).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, CREB can be activated and sustained by the CaMKII cascade (Ao, Ko, & Zhuo, ) and the activation of CREB by phosphorylation at Ser133 ( S133 p‐CREB) is critical for memory formation and LTP maintenance, because the downstream genes are involved in synaptic formation, neuronal plasticity and neurogenesis (Deisseroth et al, ). This study supports the conclusion above and provides a proof that the transcription factor CREB, part of this signaling pathway (Jalewa, Sharma, & Hölscher, ), was also re‐activated by the novel triagonist in the APP/PS1 AD mice. GSK‐3, a multifunctional kinase, phosphorylates the tau protein which aggregates to tangles in the AD brain (Perez‐Costas, Gandy, Melendez‐Ferro, Roberts, & Bijur, ).…”
Section: Discussionsupporting
confidence: 88%
“…Novel dual GLP-1/GIP receptor agonists have the advantage of activating two signaling pathways, and have been shown to be superior to single GLP-1 receptor agonists [31,61]. We previously reported that another dual agonists named DA-JC1 showed good neuroprotective effects in the MPTP mouse model of Parkinson's disease [33,62].…”
Section: Discussionmentioning
confidence: 99%
“…These dual receptor agonists show superior effects to single GLP-1 analogues such as liraglutide (Finan et al, 2013). We tested a novel dual agonist (DA-JC1) in rotenone stressed SH-SY5Y cells and demonstrated that it was cytoprotective at much lower doses than single GLP-1 or GIP receptor agonists (Jalewa et al, 2016). We furthermore tested DA-JC1 in the MPTP mouse model of PD, which showed some protective effect but which was not superior to liraglutide (Cao et al, 2016;Ji et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%